A estrutura de metacomunidades de peixes em um sistema natural preservado. O caso da planície de inundação do rio Ivinhema, Brasil. - Message, Hugo José (2011)
Flood pulses are the main structuring forcing function in the aquatic environments of floodplain, shaping the conditions of the environments and of the organisms inhabiting them. Thus, during the floods, the biotopes of a floodplain are connected and environmental variables are homogenized, favoring the movements of the fish assemblage onto the plain (interaction of the local assemblage with the regional species pool). In this paper, it was considered the possibility of the metacommunities species-sorting perspective in explaining the structure of the fish assemblage of the Ivinhema River. I tested the hypothesis that the structure of the fish assemblages of the Ivinhema River are determined by the positive relation between species compostion and the environmental variation in all lower the region and that the hydrological cycle plays a fundamental role in determining such variations. There were significant temporal variations, but not spatial, in the considered environmental variables and the fish assemblage structure. Yet, during the flood period, limnological variables were more similar among the environments and very different from the other months. After the flood, there was a tendency of separation in the two other months but still with no significant differences in the spatial scale within the months. Finally, linear regression showed that the fish assemblages are well related to the environmental variables, but the local variations (in limnological variables) are not directly linked to the fish assemblages; they appear to function as an intermediate factor in the process. Thus, the structuring of fish assemblages studied follow the species-sorting model, where the metacomunidade (fish assemblage) are linked by dispersal, which enable the response of the assemblages structure by environmental conditions and their influence on the ecological relations between fishes in the region.